Expression Levels of Three Key Genes CCNB1, CDC20, and CENPF in HCC Are Associated With Antitumor Immunity - Si, Tengfei; Huang, Zhenlin; Jiang, Yuanhang; Walker-Jacobs, Abigail; Gill, Shaqira; Hegarty, Robert; Hamza, Mohammad; Khorsandi, Shirin Elizabeth; Jassem, Wayel; Heaton, Nigel; Ma, Yun (Frontiers in Oncology, 2021)
Introduction: Hepatocellular carcinoma (HCC) is the most common primary liver cancer. The development of diagnostic programs and new treatments targeting common genetic events in the carcinogenic process are providing further insights into the management of HCC. The aim of this study was firstly to validate key genes that are involved in promoting HCC development and as biomarkers for early diagnosis; secondly to define their links with antitumor immunity including inhibitory checkpoints. Methods: Multiple databases including GEO, GEPIA, Kaplan Meier Plotter, UALCAN and Oncomine were used for target genes screening and establishment of a co-expression network. Data of 367 HCC patients were downloaded from TCGA data-base. The diagnostic and prognostic value of screened genes were tested by ROC curve and correlation analysis. The links with the key genes in HCC and antitumor immunity were defined using both blood and liver tissue collected prospectively from HCC patients in our center. Results: Up-regulation of CCNB1, CDC20 and CENPF were observed in HCC and are involved in the p53 signal pathway. The hepatic mRNA expression levels of these three genes were strongly associated with patients’ prognosis and expressed high value of AUC. Also, these three genes were positively correlated with the gene expression of IFN-, TNF- and IL-17 in peripheral blood. In addition, the expression of CENPF showed positive correlation with the percentage of CD8pos T cells and negative correlation with the percentage of CD4pos T cells in the peripheral blood. In the HCC microenvironment, the transcript levels of these three genes and inhibitory checkpoint molecules including PD-1, CTLA-4 and TIM-3 were positively correlated. Conclusion: The upregulation of CCNB1 and CDC20 and CENPF genes was a common event in hepatocarcinogenesis. Expression levels of three genes showed potential for diagnosis and prognosis in HCC. There is a close association between three genes and Th1/Th17 cytokines as well as the count of CD4pos and CD8pos T cells. The positive correlation between the three genes and inhibitory checkpoint genes, PD-1, CTLA-4 and TIM-3, indicates that these genes are linked with weakened antitumor immunity in HCC. Our findings may provide further insights in developing novel therapies for HCC.